Informatics-Driven Therapeutic Innovations in Autism Spectrum Disorder: Videogames, Extended Reality, and Health IT Integration - Fodale, Michele Francesco; Signer, Maria Rosa (LPPM Universitas Andalas, 2025)
Autism Spectrum Disorder (ASD) presents multifactorial challenges in diagnosis, therapeutic delivery, and long-term care coordination. Informatics-driven therapeutic approaches including videogame-based interventions, extended reality (XR), and artificial intelligence (AI)-enhanced systems have emerged as promising modalities to address the sensory, cognitive, and behavioral complexity of ASD. This systematic review consolidates findings from 34 peer-reviewed studies (2012–2025), emphasizing the role of Health Information Technology (Health IT) infrastructures in the design, interoperability, and clinical validation of digital therapeutics.Results demonstrate that 76% of the analyzed studies report statistically significant pre–post intervention improvements in social, motor, or cognitive performance. Technical architectures commonly rely on FHIR-based interoperability, SNOMED CT semantic encoding, and HIPAA/GDPR-compliant data pipelines. Limitations include data scarcity, lack of large-scale randomized trials, usability constraints, and incomplete EHR integration. The review concludes that scalable ASD care requires unified Health IT ecosystems embedding AI, serious gaming, and extended reality through secure, interoperable, and ethically governed informatics frameworks.